Contribution of BARI cereal crops to the national GDP of Bangladesh - Karim, MR; Baset, MA; Alam, QM; Hossain, S (Bangladesh Journal of Agricultural Research, 2009)
The study was conducted to estimate the contribution made by BARI cereal crops to GDP in the national economy of Bangladesh during the financial year 2005-2006. For the purpose of GDP calculation of BARI cereal crops, both primary and secondary data were collected from the concerned scientists of BARI, BBS, and DAM. Bangladesh has produced total goods and services those valuation at constant market price of Tk. 3150370.14 million in the financial year 2005-2006, where the contribution of agriculture and forestry was found Tk. 467436.18 million. Primarily producers sell their crops to the different users at farm-gate price and then the final output flour, bread, biscuit, poultry feed and its by-product straw, cattle feed, fuel and fodder for further value added when it is marketed to the consumer via a number of intermediaries. The value added price of the goods and services of BARI cereal crops were found at constant market price of Tk. 31434.75 million that comes as GDP valuation to the national economy. Finally, the contribution of BARI cereal crops to the agricultural and forestry GDP as worked out at 6.72 percent. On the other hand, contribution to GDP of BARI cereal crop technologies was found to be 4.40 percent. Key Words: Contribution, BARI cereal, national GDP. doi: 10.3329/bjar.v33i4.2289 Bangladesh J. Agril. Res. 33(4) : 565-570, December 2008